IMPROVING INTERPERSONAL COMMUNICATION BETWEEN PARENTS AND CHILDREN THROUGH EDUCATIONAL GAME TOOLS - Wahdiyati, Dini; Romadlan, Said; Maududi, Mukhlish Muhammad; Yunan, Zulfahmi Yasir (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
The era of disruption caused fundamental changes in society, including in the pattern of family communication and the education system. Parents are busy with their work, while children have to study at school, causing interpersonal communication between parents and children to become less intense. In fact, interpersonal communication between parents and children plays an important role in children's success in learning, reducing stress, and determining children's future. Therefore, it is necessary to revitalize interpersonal communication between parents and children. The purpose of this community partnership program is to help revitalize interpersonal communication between parents and children by utilizing Educational Game Tools. This community partnership program offers a solution to overcome the problem of interpersonal communication between parents and children through a fun educational game approach as well as to reduce the pressure on children due to the burden of learning at school to partners, namely Cahaya Ria Kindergarten, in Ciledug, Tangerang. The results of this program show that the educational game approach is able to build interpersonal communication between parents and children. In addition, this program also can help children overcome learning pressure at school, and is able to reduce children's dependence on the use of gadgets.